PENGARUH LINGKUNGAN SOSIAL, TINGKAT PENDAPATAN DAN PERKEMBANGAN TEKNOLOGI TERHADAP PERILAKU KONSUMTIF MASYARAKAT DESA GLONDONG, KAB. BLITAR DENGAN GAYA HIDUP SEBAGAI VARIABEL MODERASI A1 DELF PADA WEBSITE: WWW.KWIZIQ.COM - Dwi Rahayu, Diah; Anas, M.; Muchson, M. (JURNAL ILMIAH EDUNOMIKA, 2024)
The aim of this research is to find out whether there is an influence of the social environment, income level and technological developments on people's consumptive behavior with lifestyle as a moderating variable. This research uses a descriptive quantitative approach, for data collection using questionnaires with a sample of 373 people. This research uses SMART PLS software in data processing. The significant value obtained: the social environment has a positive influence and is stated to be significant with consumer behavior in this relationship t statistic 4,680>1.96 and P value 0.0001.96 and the P value is 0.0001.96 and the P value is 0.0301.96 and the P value is 0.0001.96 and the P value is 0.0141.96 and the P value is 0.000